Mindfulness, cognitive load, and performance: examining the interplay of stress and self-regulation in physical education - Songhu Kong; Lingling Qiu; Yangyang Su; Yibo Zhang; Kaiye Sun (BMC Psychology)
Abstract Purpose This study investigates the role of mindfulness practices and self-regulation in reducing cognitive load stress and enhancing physical performance among university students in physical education. Using a comprehensive structural model, the research explains the mediating effect of cognitive load stress and the moderating role of self-regulation in these relationships. Methods Data collected from 498 students were analyzed using partial least squares structural equation modeling, ensuring robust measurement and predictive validity. Results The findings reveal that mindfulness practices significantly reduce cognitive load stress and directly enhance physical performance. Besides, cognitive load stress acts as a mechanism through which mindfulness improves performance, indicating an indirect effect. Moreover, self-regulation strengthens both the direct and indirect pathways, highlighting its role in shaping these relationships. Conclusion The study contributes to goal-setting theory and stress and coping theory by clarifying the mechanisms linking mental strategies to physical outcomes. Implications Practical implications suggest integrating mindfulness and self-regulation strategies into physical education programs to foster improved performance and well-being. These insights highlight the value of holistic approaches in educational settings.